Resilient teachers. Central elements in the University tutoring program - Cajigal Molina, Erick (IE Revista de Investigación Educativa de la REDIECH, 2021)
Resilience can be developed in the universities spaces designated for tutoring program, and it affects the students’ failure and desertion rate. Professors are more likely to participate in developing or enhancing students’ resilience by being resilient themselves. Hence, an investigation carried out with the objective of knowing the state of the aspects that make up the resilience of a group of Professors from the Universidad Autónoma del Carmen, Mexico, in 2020. It is a correlational quantitative study. The instrument used is the survey for education tutors, which was subjected to Cronbach’s Alpha test, resulting in high reliability. The information was processed in the SPSS software, the description of the items was carried out by means of frequencies and variables were crossed with Pearson’s Chi-square statistical test. The results show that the participants have acceptable resilience, which gives them the opportunity to participate in a relevant way in the development of their students resilience. However, areas of opportunity are identified in teachers that prevent them from positioning themselves in the desirable standards and that must be addressed.